2019
DOI: 10.1021/acs.orglett.9b00532
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Strategy for the Construction of Functionalized Triphenylene Frameworks via Palladium Catalyzed Intramolecular Annulation/Decyanogenative C–H Bond Alkenylation

Abstract: The palladium catalyzed synthesis of 14-phenylbenzo­[f]­tetraphene-9-carbonitrile derivatives as core polycyclic aromatic hydrocarbons (PAHs) was achieved via an intramolecular annulation and decyanogenative C–H bond alkenylation strategy. A readily synthesized Knoevenagel condensation product of [1,1′-biphenyl]-2,2′-dicarbaldehyde with benzyl cyanide converted successfully into 14-phenylbenzo­[f]­tetraphene-9-carbonitrile derivatives in excellent yields up to 94%. The transformation involves an intramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…During the last two decades, C–H activation chemistry has gained widespread attention, because it provides an atom- and step-economical route for preparing not only complex molecules, such as natural products and pharmaceuticals, but also fluorophores that can be applied in organic light-emitting diodes (OLEDs). In the field of C–H activation chemistry, C–C bond formation has been mainly studied so far, but recently, direct C–H amination/amidation strategies resulting in C–N bond formation have also been actively investigated. Among them, Chang’s group developed iridium-catalyzed direct C–H amidation (DCA) reactions between sulfonyl azides and arenes containing carbonyl (or imine) directing groups, thus enabling efficient synthesis of various sulfonamides under mild conditions (Scheme a). ,, Inspired by the highly efficient DCA, we recently reported direct C–H amidation polymerization (DCAP) of bis-sulfonyl azides and bis-benzamides to produce polysulfonamides by an atom-economical and green method (Scheme b). , Interestingly, unique intramolecular hydrogen-bonds are formed between the proton on the sulfonamide group and adjacent carbonyl group throughout the polymer backbone, causing polysulfonamides to undergo an excited-state intramolecular proton-transfer (ESIPT) process and emit blue-light with high quantum yields. This process occurs when photoexcited molecule emits light with a very large Stokes shift by transfer of protons, leading to keto–enol tautomerization.…”
mentioning
confidence: 99%
“…During the last two decades, C–H activation chemistry has gained widespread attention, because it provides an atom- and step-economical route for preparing not only complex molecules, such as natural products and pharmaceuticals, but also fluorophores that can be applied in organic light-emitting diodes (OLEDs). In the field of C–H activation chemistry, C–C bond formation has been mainly studied so far, but recently, direct C–H amination/amidation strategies resulting in C–N bond formation have also been actively investigated. Among them, Chang’s group developed iridium-catalyzed direct C–H amidation (DCA) reactions between sulfonyl azides and arenes containing carbonyl (or imine) directing groups, thus enabling efficient synthesis of various sulfonamides under mild conditions (Scheme a). ,, Inspired by the highly efficient DCA, we recently reported direct C–H amidation polymerization (DCAP) of bis-sulfonyl azides and bis-benzamides to produce polysulfonamides by an atom-economical and green method (Scheme b). , Interestingly, unique intramolecular hydrogen-bonds are formed between the proton on the sulfonamide group and adjacent carbonyl group throughout the polymer backbone, causing polysulfonamides to undergo an excited-state intramolecular proton-transfer (ESIPT) process and emit blue-light with high quantum yields. This process occurs when photoexcited molecule emits light with a very large Stokes shift by transfer of protons, leading to keto–enol tautomerization.…”
mentioning
confidence: 99%
“…In other words, ligands, much like a chemist's hands, manipulate the reactivity and selectivity in metal catalysis. 4 Therefore, the ligand-enabled divergent synthesis strategy has attracted more and more attention, and several reviews and literature reports involving divergent synthesis have been reported by organic chemists. 5 For example, Kong and co-workers recently reported advances in Ni-catalyzed ligand-controlled divergent and selective synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) have gained considerable attention due to their outstanding electrochemical and photophysical properties and widespread applications in optical, organic and electronic materials. [1] In particular, phenanthrene-based PAHs (Scheme 1a), such as benzo [b]triphenylenes, [2] exhibit excellent photochemical properties, good stability under irradiation and have been described as useful singlet oxygen photosensitizers and components of semiconductor devices. [3] A plethora of synthetic approaches to these PAHs have been reported, including aryne cyclotrimerizations, oxidative cyclizations, cycloadditions, cross-coupling reactions and CÀ H activation.…”
Section: Introductionmentioning
confidence: 99%